2020
DOI: 10.3390/molecules25143261
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polypeptide Antibiotic Residues in Food of Animal Origin by Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry

Abstract: A novel UHPLC-MS/MS method for the determination of polypeptide antibiotic residues in animal muscle, milk, and eggs was developed and validated. Bacitracin A, colistin A, colistin B, polymyxin B1, and polymyxin B2 were extracted from the samples with a mixture of acetonitrile/water/ammonia solution 25%, 80/10/10 (v/v/v), and put through further evaporation, reconstitution, and filtration steps. The chromatographic separation was performed on a C18 column in gradient elution mode. Mass spectral acquisitions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It was further modified after studying the core literature using LC–MS/MS for polypeptide antibiotics determination in animal origin food. The published literature for sample preparation primarily discusses the deproteinization step (referred to as acidic pretreatment), performed with the help of organic solvents (acetonitrile and methanol) and acids (trichloroacetic acid and hydrochloric acid) in varied combinations, as shown in Table 3 [ 2 , 9 , 10 , 11 , 12 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was further modified after studying the core literature using LC–MS/MS for polypeptide antibiotics determination in animal origin food. The published literature for sample preparation primarily discusses the deproteinization step (referred to as acidic pretreatment), performed with the help of organic solvents (acetonitrile and methanol) and acids (trichloroacetic acid and hydrochloric acid) in varied combinations, as shown in Table 3 [ 2 , 9 , 10 , 11 , 12 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Colistin is a cationic peptide antibiotic with weak acid (carboxylic acid) and base (amino) functional groups. Bladek et al [ 2 ] have reported that colistin could be found in three forms—deprotonated base form, neutral form or protonated acid form. Colistin is highly polar in nature, hence why in the present study polar extraction solvents i.e., methanol and acidified water, were used [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations